'We are not anything alike': marginalization of health professionals with disabilities. Issue 5 (28th May 2017) - Bulk, Laura Yvonne; Easterbrook, Adam; Roberts, Earllene; Groening, Marlee; Murphy, Susan; Lee, Michael; Ghanouni, Parisa; Gagnon, Jennifer; Jarus, Tal
Abstract: Despite inclusive rhetoric, disabled peoples' participation in the Health and Human Service (HHS) professions remains limited. This study explores the perspectives of individuals in the HHS sector regarding inclusion-related barriers and facilitators. We found three mechanisms that marginalize disabled people in HHS education and professions: dominant disabling discourses; discriminatory design within programmes and universities; and oppressive interactions. The inclusion of disabled individuals is vital for ensuring HHS professionals represent the populations they serve. By challenging the views of educators, professionals, and scholars, these findings may become part of the foundation upon which change can be created.